Tingkat kompetensi literasi digital ditinjau dari gaya belajar peserta didik sekolah dasar muatan globalisasi - Wijaya, Said Agil Rengga; Mahfud, Hasan; Surya, Anesa (Didaktika Dwija Indria, 2024)
Abstract. This research aims to describe the level of competence of digital literacy of students from the learning style on the globalization content of students in grade VI SD Djama'atul Ichwan Surakarta. This research uses a qualitative research approach with case study methods. The data source in this study came from students in grade VI of SD Djama'atul Ichwan Surakarta with a sample of 9 students with the provision of 3 learning styles of students, each numbering 3 subjects of students. Sampling technique is done by purposive sampling. Data collection techniques in this research include observation, interview and documentation studies. The data validity techniques used by triangulation techniques are triangulation techniques and time triangulation. The data was analyzed using the Creswell analysis model. The results of this research show that students with a visual learning style have the highest level of digital literacy competence then followed by students with an auditory learning style and students with a kinesthetic learning style. The theoretical implication of this research is that it can be an additional information and basic material for the development of research that will be carried out next, especially regarding the level of digital literacy competence of students who are reviewed from the learning style. In addition, the practical implication of this research is that it can be an exercise as well as knowing what the level of digital literacy competence is owned by students at the current elementary school level.Keywords: digital literacy, learning styles, visual, auditory, kinesthetic, elementary school